Biocompatibility of two current adhesive resins - De Souza Costa, Carlos Alberto [UNESP]; Teixeira, Hilcia Mezzalira [UNESP]; Batista Lopes Do Nascimento, Alexandre; Hebling, Josimeri [UNESP] (Wolters Kluwer, 2000)
The purpose of the study was to evaluate the biocompatibility of two current adhesive resins and a calcium hydroxide cement. Fifty-four polyethylene tubes were filled with these dental materials, which were hand-mixed or light-cured according to the manufacturer's directions: group 1-Clearfill Liner Bond 2 (Kuraray); group 2-Single Bond (3M); and group 3-calcium hydroxide cement (Dycal-Dentsply). The materials were implanted into dorsal connective tissue of rats, which were killed 7, 30, and 60 days after the implantation procedure. The implant sites were excised, immersed in buffered Karnovsky's fixative, and processed using routine histological techniques. Sections of 6 μm thickness were stained with hematoxylin and eosin and assessed under light microscopy. Both adhesive resins at 7 days elicited a moderate/intense inflammatory reaction that decreased over time. Fibrous capsules surrounding the tubes were observed at 30 days. Half of the samples in groups 1 and 2 showed thin fibrous capsule formation containing macrophages, capillaries, lymphocytes, fibroblasts, and collagen fibers. Connective tissue healing was observed even though many specimens exhibited a persistent inflammatory reaction mediated by macrophages and giant cells at the 60-day evaluation. Dycal allowed complete healing at 30 days with only a thin fibrous capsule. In conclusion, all experimental materials were successfully walled off by the connective tissue of the rat. However the adhesive resins may release particulates that may, in turn, induce a persistent local inflammatory reaction. Consequently, in this specific condition, these materials cannot be regarded as biocompatible. Dycal was less irritating than the adhesive resins and was better tolerated by the connective tissue. Copyright © 2000 by The American Association of Endodontists.